LRBA organizes distinct vesicular trafficking systems in distal nephron segments for water and sodium conservation - Kanako Nagaoka; Fumiaki Ando; Tamami Fujiki; Hassan Abolhassani; Yu Hara; Hideki Yanagawa; Soichiro Suzuki; Yuriko Sakamaki; Daisuke Oikawa; Hiroaki Kikuchi; Shintaro Mandai; Yutaro Mori; et al. (Proceedings of the National Academy of Sciences, 2026)
Lipopolysaccharide-responsive and beige-like anchor protein (LRBA) deficiency is a rare genetic disorder characterized by immune dysregulation. The immune checkpoint molecule cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) fails to perform proper membrane trafficking in the absence of LRBA. In addition to immune cells, LRBA localizes to intracellular vesicles in various epithelial cells; however, its physiological roles have not been accurately deciphered. It was observed in this study that LRBA facilitates water and sodium transport by promoting vesicular trafficking of aquaporin-2 (AQP2) and AQP4 in renal collecting duct cells and that of sterile 20/SPS1-related proline/alanine-rich kinase (SPAK) in distal convoluted tubule cells. Consequently, Lrba knockout mice exhibited vasopressin-resistant polyuria and hypotension under sodium-restricted conditions. This registry study revealed a polyuric phenotype in a subset of patients with LRBA deficiency, characterized by inappropriately low urine specific gravity despite the presence of chronic diarrhea. Notably, desmopressin treatment ameliorated impaired urinary concentration in a mouse model of human LRBA deficiency. LRBA functions as a central coordinator of fluid and sodium homeostasis by organizing segment-specific vesicular trafficking systems in renal epithelial cells.